KEKERASAN TERHADAP ETNIS TIONGHOA DI PADANG MEI 1998 - DESMARISA, RINI - (Pendidikan Sejarah, 2014)
This thesis examines the Violence on Tionghoa Ethnic In Padang on May 1998. This thesis examined about the violence on Tionghoa ethnic. The main problems of this research are ( 1 ) what did the factors cause the violence on Tionghoa ethnic in Padang on May 1998. ( 2 ) how did the violence toward Tionghoa ethnic happen in Padang on May 1998. ( 3 ) how was the effect of violence on Tionghoa ethnic in Padang on May 1998 in social and economics field. ( 4 ) how was the effect of the May 1998 tragedy in Padang generally. This research used method consisting on four stages namely ( 1 ) is heuristic ir collecting the sources to get all relevant sources by using primary data such as document and interview with people who involved directly in this problem. ( 2 ) is conducting source critics internally and externally after getting the data by conducting authenticity and validity of data whether the data is relevant or not. ( 3 ) is conducting analysis and interpretation (interpretation about the data collected). There was the relevant separation and selection and verifiable. And ( 4 ) the writer showed the research result in a form of thesis. The research result showed that the violence on Tionghoa ethnic started from monetary crises that happened in Indonesia and starting demonstration done by university students and demanded the decline of President Soeharto as the President of Indonesia because he was regarded had no longer ability to lead Indonesia. The university students plundered, burned and destroyed. It can be concluded, the violence on Tionghoa ethnics happened because of social jealousy between Tionghoa and indigenous people. Indigenous people were jealous to see the success on Tionghoa ethnic especially in trading.